Prognostic Value of White-Coat and Masked Hypertension Diagnosed by Ambulatory Monitoring in Initially Untreated Subjects: An Updated Meta Analysis - Pierdomenico, Sante D.; Cuccurullo, Franco (American journal of hypertension, 2011)
Background The prognostic relevance of white-coat hypertension (WCH) and masked hypertension (MH) is controversial. The aim of this study was to perform an updated meta-analysis on the prognostic value of WCH and MH diagnosed by ambulatory monitoring in initially untreated subjects. Methods We searched for articles evaluating cardiovascular outcome in WCH or MH or sustained hypertension (SH) in comparison with normotension, investigating untreated subjects at baseline or performing separate analysis for untreated or treated subjects, and reporting adjusted hazard ratio (HR) and 95% confidence interval (CI). Results Eight studies were identified. Five whole studies and untreated groups of three others were included in the meta-analysis. The pooled population consisted of 7,961 subjects who experienced 696 events. When compared with normotension, the overall adjusted HR was 0.96 (95% CI 0.65-1.42) for WCH (P = 0.85), 2.09 (1.55-2.81) for MH (P = 0.0001), and 2.59 (2.0-3.35) for SH (P = 0.0001). There was no significant difference between WCH and normotension according to normotensive subjects source (same or different study population) and follow-up length. Where reported, prevalence of drug therapy was higher in subjects with WCH than in those with normotension at follow-up. Conclusion Cardiovascular risk is not significantly different between WCH and normotension, regardless of normotensive population type and follow-up length. However, at follow-up drug therapy was more frequent in WCH than in normotension and its possible impact on outcome should be evaluated in future studies. MH shows significantly higher risk than normotension, although the best way for its detection and treatment remains to be established. American Journal of Hypertension, advance online publication 16 September 2010; doi:10.1038/ajh.2010.203